The Operator 4.0: Towards socially sustainable factories of the future. (January 2020) - Romero, David; Stahre, Johan; Taisch, Marco
Abstract: Humans are all makers of a sort. The tools we operate constantly leverage our human capabilities and evolve over history to take advantage of any innovation or a new source of power that emerges. Human-Technology Symbiosis has always been the basis for leaps in human prosperity. As we are presently in the Fourth Industrial Revolution, or Industry 4.0, it is important to focus on challenges and opportunities of contemporary work-life. Here we find the worker, the operator, benefitting from cyber-physical systems technology, connectivity, and global information networks while retaining human strengths and weaknesses. This special issue will describe the implications of a new breed of the manufacturing worker, "The Operator 4.0". The 13 contributions in this special issue will take us from the early anthropocentric organisational models to the emerging connected and cyber-physically enhanced "Operator 4.0" in highly dynamic work environments. Methods and tools for development and analysis of complex work will support the scholar or practitioner that would like to dig deeper into the future of the potential work-life of the Operator 4.0.